2014
DOI: 10.1007/s12262-014-1080-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Prospective Controlled Trial of Topical 2 % Diltiazem Versus Lateral Internal Sphincterotomy for the Treatment of Chronic Fissure in Ano

Abstract: Fissure in ano is a very common disorder of the anorectal region. Internal sphincter hypertonia with decreased relaxation coupled with mucosal ischemia of posterior anal canal are the major pathologies in chronic anal fissure (CAF). Though lateral internal sphincterotomy (LIS) remains the gold standard of treatment for the disease, it is accompanied by the potential complication of incontinence to both flatus and faecal matter. The aim of our study was to explore the role of topical diltiazem as an effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Similar to the urethra, the NK 2 receptors are likely present in the internal anal sphincter (Tichenor et al 2002), where their activation may keep the sphincter tight, thus providing resistance to defecation. Future studies would need to investigate the role of these receptors in decreasing defecation efficiency and whether sphincter relaxants (such as phosphodiesterase inhibitors, topical diltiazem, a calcium channel blocker, botulinum toxin A injection and other) would provide additional benefits (Ballester et al 2007; Gandomkar et al 2015; Jones et al 2002; Vaithianathan and Panneerselvam 2015). While we did not assess defecation in this study, pilot studies in chronic SCI rats showed that LMN-NKA reliably induces defecation (in progress L. Marson), suggesting that if stools were present in the rectum, both urine and stools would be excreted (sitting on a toilet to urinate would be advisable).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the urethra, the NK 2 receptors are likely present in the internal anal sphincter (Tichenor et al 2002), where their activation may keep the sphincter tight, thus providing resistance to defecation. Future studies would need to investigate the role of these receptors in decreasing defecation efficiency and whether sphincter relaxants (such as phosphodiesterase inhibitors, topical diltiazem, a calcium channel blocker, botulinum toxin A injection and other) would provide additional benefits (Ballester et al 2007; Gandomkar et al 2015; Jones et al 2002; Vaithianathan and Panneerselvam 2015). While we did not assess defecation in this study, pilot studies in chronic SCI rats showed that LMN-NKA reliably induces defecation (in progress L. Marson), suggesting that if stools were present in the rectum, both urine and stools would be excreted (sitting on a toilet to urinate would be advisable).…”
Section: Discussionmentioning
confidence: 99%
“…Anal fissure is one of the most common diseases of the anorectal region that is frequently encountered in surgical practice (1). It is a longitudinal rupture of the stratified squamous epithelial tissue formed in the anoderm distal to the dentate line and is generally located on the middle line posterior to the anus (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…one study showed favorable results in manual dilatation of anus as in our study 14 but vaithiancithan reported one patients with this complications. 15 In our study we did not faced fecal incontinence in manual dilatation of anus.…”
Section: Discussionmentioning
confidence: 63%